2019
DOI: 10.1039/c9an01680e
|View full text |Cite
|
Sign up to set email alerts
|

A label-free fluorescent sensor based on silicon quantum dots–MnO2 nanosheets for the detection of α-glucosidase and its inhibitor

Abstract: We have successfully designed a fluorescence SiQD–MnO2 nanosheet sensing platform to detect α-glucosidase and acarbose for the first time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 30 publications
1
15
0
Order By: Relevance
“…This is ascribed to that the sulfydryl in MTG is reductive and MnO 2 nanosheets can be decomposed by reductive substances. [36][37][38] The decomposition of MnO 2 nanosheets by MTG was further demonstrated by TEM ( Figure S1). It can be observed that the two-dimensional structure of MnO 2 nanosheets is destroyed after the addition of MTG.…”
Section: Decomposition Of Mno 2 Nanosheets By Mtgmentioning
confidence: 94%
See 1 more Smart Citation
“…This is ascribed to that the sulfydryl in MTG is reductive and MnO 2 nanosheets can be decomposed by reductive substances. [36][37][38] The decomposition of MnO 2 nanosheets by MTG was further demonstrated by TEM ( Figure S1). It can be observed that the two-dimensional structure of MnO 2 nanosheets is destroyed after the addition of MTG.…”
Section: Decomposition Of Mno 2 Nanosheets By Mtgmentioning
confidence: 94%
“…MnO 2 nanomaterials can also be decomposed by reductive substances such as sulfydryl compounds, H 2 O 2 and ascorbic acid into Mn 2 + , resulting in a color change from brown to colorless. [36][37][38] Further considering the interaction of sulfhydryl with Hg 2 + , it is speculated that Hg 2 + can be colorimetrically detected based on the inhibited decomposition ability of sulfhydryl toward MnO 2 nanosheets.…”
Section: Introductionmentioning
confidence: 99%
“…According to previously reported studies, acarbose was commonly used as an anti-diabetic drug to precisely inhibit the catalytic activity of α-Glu. 9 Hence, the designed colorimetric and fluorometric assays of α-Glu activity have been performed to study the enzymatic inhibition ability using acarbose as a model. Once α-Glu was oppressed to acarbose, the catalytic hydrolysis of 4-HPαDG was refrained, which ended up by the decreased ability to generate HQ.…”
Section: Stability Of Simentioning
confidence: 99%
“…12,13 More particularly, due to their harmlessness and low toxicity, Si-based nanosensors could be used in human body as markers. 9,14 Thus, Si CNPs reveal an extensive dominance in biosensing and bioimaging. 15 Although an impressive progress for the preparation of Si CNPs has been achieved, however, the preparation procedures under tolerable parameters are still desirable.…”
Section: Introductionmentioning
confidence: 99%
“…Electrochemical and oxidative properties of Mn oxides predestine them to be used as a component of nanocomposites, sensitive to a broad range of compounds. MnO 2 —based biosensors can detect, i.a., α-glucosidase, glucose, or glutathione (GSH) in human blood [ 19 , 20 , 21 ] or Salmonella typhimurium , a pathogenic bacterium, in food products [ 22 ].…”
Section: Introductionmentioning
confidence: 99%